Transcendent development : the ethics of universal dignity - Thakhathi, Andani (Emerald Publishing Limited, 2022)
Is it possible for Africa to rise above its present unfulfilling conditions for good? Can poverty, inequality, corruption, maladministration, and intolerance be overcome? This special volume of Research in Ethical Issues in Organizations argues that it certainly is. The epoch of Transcendent Development has arrived, and an authentic African philosophy is at hand to understand it. In this landmark scholarly anthology, seven chapters blaze a trail towards an African philosophical ethos for organisational and business ethics rooted in the complex South African experience. With almost unmatched sociocultural diversity, South Africa is an ideal melting pot for the great unity-in-diversity experiment of Universal Dignity. If the disparate people of planet earth have any fighting chance of averting the looming dystopian existential crisis inherent in unsustainable development, the hopes thereof begin in the South. Identity-based polarisation and its attendant torment of destructive strife must be exchanged for a mutually beneficial ethos of fulfilment, that truly "leaves no one behind". This volume offers meaningful pathways to this haven of "Ubuntu". Edited by Dr. Andani Thakhathi, this special volume of seven chapters presents insightful gems of wisdom that clarify how the self-fulfilling cycle of "Compound-Indignity" may be overcome through the systematic operationalisation of Bantu Wisdom as Transcendent Development. Collectively, the chapters in this special volume contain morally courageous, creative storytelling prose offering paradigm shifts, empirical evidence and surprising "antenarratives" that explain how a harmonious Africa may be realised, starting in the Mother Continent's Southern-most tip.
Includes index.
Keywords: Business ethics -- South Africa.; Social responsibility of business -- South Africa.; Economic development -- South Africa.; Business & Economics -- Business Ethics.; Business ethics & social responsibility.; elektronické knihy; electronic books